Islam Berkemajuan dalam Perspektif Muhammadiyah - Hendro Widodo; Mundzirin Yusuf (Islamica: Jurnal Studi Keislaman, 2019)
This study aims to describe the progressive Islam emerging in Muhammadiyah and to elaborate it in the view of Muhammadiyah. The results of this study are: 1) Islamic terms and ideas “progressive” substantially and historically are not new, because they are attached to the presence of the Muhammadiyah since its birth, and became popular when it was used as the theme of the 47th Muhammadiyah Congress in Makassar, “Movement for Change Towards Progressive Indonesia”; 2) Progressive Islam sows the seeds of truth, kindness, peace, justice, benefit, prosperity, and the virtue of living dynamically for all humanity; Islam that upholds the glory of men and women without discrimination. Progressive Islam is a vision of Islam of Muhammadiyah that is not bound by the dimensions of space and time.